Development of research competences in undergraduate students - Aylas, Carmen Lily Winchez; Alvarez, Patricia Bejarano (Institute of Advanced Engineering and Science, 2025)
This study addresses the limited involvement of university students in research activities, which reflects a significant gap in the development of key research competencies for their academic and professional advancement. Lack of involvement restricts essential skills such as problem formulation, rigorous data analysis and communication of findings, preventing students from generating relevant knowledge and meeting the challenges of their future careers. Through a systematic review of the literature on the development of research competencies in undergraduate students, using reliable sources such as Scielo, Dialnet and other academic journals, this study identified effective methodologies to foster such competencies. Rigorous exclusion criteria were applied to ensure the relevance and timeliness of the selected studies. In conclusion, educational strategies such as flipped learning and research workshops were found to have a positive impact on the development of research competences, enhancing both technical and transversal skills, such as innovation and critical thinking. These methodologies prepare students for academic and professional challenges and foster a research culture in educational institutions. This article explicitly identifies and synthesizes innovative educational strategies (flipped learning, Lean startup, and research workshops) that have a proven impact on strengthening both technical and transversal research competences in undergraduates in Latin America. This systematic approach and regional focus are not found in prior reviews.